Creatine supplementation patterns and perceived effects in select division I collegiate athletes - Greenwood, M.; Farris, J.; Kreider, R.; Greenwood, L.; Byars, A. (Clinical Journal of Sport Medicine, 2000)
OBJECTIVE: To describe patterns of creatine use in select Division I collegiate athletes based on recommended dosages according to body weight. Further, to report the perceived effects noted with creatine supplementation. DESIGN: Anonymous open-ended self-report descriptive questionnaire. SETTING: National Collegiate Athletic 94Association Division I institution. PARTICIPANTS: Two-hundred and nineteen male and female collegiate athletes representing eight varsity sports. MAIN OUTCOME MEASURE(S): An open-ended questionnaire was administered to determine patterns of creatine use during the loading and maintenance phases of this nutritional supplement. In addition, perceived positive, negative, and no effects associated with creatine usage patterns were determined from athlete responses on this self-report measure. RESULTS: Considering this select group of collegiate athletes, highly variable patterns of creatine supplementation were noted for loading/maintenance phases based on recommended dosages/days and body weight. Of the 219 athletes surveyed, 90 (41%) reported using creatine, while creatine supplementation was more prevalent among men than women. Creatine users (80 athletes, 89%) reporting perceived positive effects were primarily at or below recommended dosages for the loading phase but above recommended dosages in the maintenance phase. Creatine users (34 athletes, 38%) reporting perceived negative effects were primarily at or below recommended dosages in the loading phase but noticeably above recommended dosages in the maintenance phase. Ironically, all creatine users who reported negative side effects also reported positive effects. Creatine users (10 athletes, 11%) reporting no effects were below recommended loading dosages but above recommended maintenance dosages. CONCLUSIONS: The perceived positive effects noted support current research (strength/weight gains), while the perceived negative effects (cramping/gastrointestinal distress) were consistent with anecdotal reports surrounding creatine supplementation. Apparently, collegiate athletes in this study are in need of education regarding the proper use of creatine supplementation. Additional studies are needed to ascertain creatine supplementation patterns of collegiate athletes in various settings.